Effectiveness of repetitive transcranial magnetic stimulation on hypomimia induced sialorrhea among Parkinsons: a case study - Ramesh, Subramaniyan; Das, Kishoremoy; Srinivasan, Vignesh; Suganthirababu, Prathap (International Journal of Research in Medical Sciences, 2025)
Excessive drooling (sialorrhea) in Parkinson’s disease (PD) affects quality of life, often linked to hypomimia. Conventional treatments have limitations, while repetitive transcranial magnetic stimulation (rTMS) shows promise but remains understudied for sialorrhea. A 74-year-old male with PD underwent rTMS and exercise therapy for eight weeks. Pre-treatment scores were 63 in sialorrhea clinical scale for PD and 7 on the Radboud oral motor inventory for PD (ROMP), improving to 48 and 5. Surface electromyography (SEMG) showed increased zygomaticus major activity (10.5 µV to 16.2 µV) and corrugator supercilii (17.3 µV to 22.7 µV), suggesting rTMS may improve sialorrhea and orofacial function in PD.